2011
DOI: 10.1523/jneurosci.3611-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1 Is Neuroprotective in Permanent Focal Cerebral Ischemia in Rodents

Abstract: The chemokine CX3CL1 and its receptor CX3CR1 are constitutively expressed in the nervous system. In this study, we used in vivo murine models of permanent middle cerebral artery occlusion (pMCAO) to investigate the protective potential of CX3CL1. We report that exogenous CX3CL1 reduced ischemia-induced cerebral infarct size, neurological deficits, and caspase-3 activation. CX3CL1-induced neuroprotective effects were long lasting, being observed up to 50 d after pMCAO in rats. The neuroprotective action of CX3C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
153
2
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(174 citation statements)
references
References 50 publications
12
153
2
7
Order By: Relevance
“…In addition, its role in modulation of cell metabolism (Cunha, 2001), neuron-glia communication (Boison et al, 2010), and the tuning of growth factor signaling (Gomes et al, 2011) is becoming evident. Indeed, we and others have recently shown that the chemokine CX 3 CL1 and the cytokines IL-6 and OSM are able to drive neuroprotection only in the presence of functional A 1 R (Biber et al, 2008;Lauro et al, 2008Lauro et al, , 2010Moidunny et al, 2010;Cipriani et al, 2011). In particular, IL-6 and OSM potentiate the expression and the function of neuronal A 1 R and therefore the ADO effects on neurotransmission and neuroprotection (Moidunny et al, 2010); on the other hand, CX 3 CL1 neuroprotection is due to ADO release from microglia, activation of A 1 R, and, possibly, the subsequent release of glial-soluble factors that contribute to neuroprotection (Lauro et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, its role in modulation of cell metabolism (Cunha, 2001), neuron-glia communication (Boison et al, 2010), and the tuning of growth factor signaling (Gomes et al, 2011) is becoming evident. Indeed, we and others have recently shown that the chemokine CX 3 CL1 and the cytokines IL-6 and OSM are able to drive neuroprotection only in the presence of functional A 1 R (Biber et al, 2008;Lauro et al, 2008Lauro et al, , 2010Moidunny et al, 2010;Cipriani et al, 2011). In particular, IL-6 and OSM potentiate the expression and the function of neuronal A 1 R and therefore the ADO effects on neurotransmission and neuroprotection (Moidunny et al, 2010); on the other hand, CX 3 CL1 neuroprotection is due to ADO release from microglia, activation of A 1 R, and, possibly, the subsequent release of glial-soluble factors that contribute to neuroprotection (Lauro et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Further evidence from fractalkine studies in cerebral ischemia has shown that its exogenous administration to ischemic rats or mice is neuroprotective but, in contrast, increases brain damage in cx3cl1 −/− mice. These findings strongly indicate that the absence of constitutive CX3CL1-CX3CR1 signaling changes the outcome of microglia-mediated effects during CX3CL1 administration to the ischemic brain (Cipriani et al, 2011). Taking into account these findings, microglia activation state in the healthy brain may be modulated by the CXCL1-CXCR1 axis which, in turn, will determine its activation state and functionality in the context of cerebral ischemia.…”
Section: Neuronal Loss and The Activation Of Microgliamentioning
confidence: 80%
“…The release of proinflammatory cytokines can in turn increase the neuronal damage, thus creating a vicious cycle in the course of ischemic brain injury. On the other hand, through specific chemokines and their receptors, such as CD22/CD45, CD47/ CD172a, CD200/CD200R, and CX3CL1/CX3CR1, neurons and microglia can activate a series of signaling pathways and ultimately regulate neuronal apoptosis [19][20][21].…”
Section: Discussionmentioning
confidence: 99%